Covid-19: A Reason behind Digital Education in Pakistan - Akram, Madieha; Anjum, Faiza; Batool, Zahira (Mediterranean Journal of Social Sciences, 2020)
Covid-19 is new virus that is spreading rapidly in all over the world. It is a communicable disease. World Health Organization announced social distancing to control the spread of that virus. All institutions are closed in Pakistan. Education was also effecting with this shutdown. A number of educational institutions have started digital education. Education is an important institution of socialization. Traditional education is not possible because of Covid-19. Digital education is taking its place according to the situation. An online survey was conducted to understand the acceptance level of online education in Lahore, Pakistan. A number of 240 students who were attending online classes solved the questionnaire. A software â€œStatistical package of social sciencesâ€ was used to see the distribution of the respondents. A statistical analysis showed that majority of the respondents is accepting online education according to the condition. It is suggested that Government should spread awareness regarding online education to make it more successful because it is the need of the time.